Improving Student Learning Outcomes in Social Studies Subjects Through Inquiry Model - Mohamad Alfikri; Nashrullah Nashrullah; Zulnuraini Zulnuraini; Khairunnisa Khairunnisa (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This classroom action research aimed to improve fifth-grade students' social studies learning outcomes through the implementation of an inquiry learning model at SD Inpres 1 Talise. The study employed Kemmis and McTaggart's model involving 32 students across two cycles. Data were collected through learning outcome tests, observation sheets for teacher and student activities, interviews, and documentation. Quantitative data were analyzed using percentage calculations for individual absorption and classical completeness, while qualitative data followed Miles and Huberman's interactive model. Pre-action results showed only 25% of students achieved the minimum completion criteria (KKM) with a class average of 60.68%. Following inquiry learning implementation, Cycle I demonstrated improvement with 43.75% classical completeness and 68.15% class average. Cycle II showed significant enhancement with 90.63% classical completeness and 82.5% class average, meeting the success criteria of 85% student completion. Teacher activity quality improved from 62.4% (good) in Cycle I to 95.2% (very good) in Cycle II, while student activity increased from 60.76% to 90.76%. The inquiry learning model effectively enhanced students' critical thinking skills, active participation, and conceptual understanding of social studies material, demonstrating its effectiveness in student-centered learning approaches.